ihe 2014 - 1st International Conference on the use of iPads in Higher Education: Conference Proceedings - Souleles, Nicos; Pillar, Claire (My University, 2014)
The 2013 Horizon Report identified tablet computing as a key emerging technology in Higher Education (HE). The report attributed the growth of tablet computing in HE to the incredible success of the iPad, which at the time had sold more than 85 million units and is predicted to sell over 377 million units by 2016. Laurillard (2007) aptly stated that the adoption process for a new technology often begins as a solution devised for non-instructional requirements (communication, entertainment, etc.) in search of a problem it can solve in education. Considering the large number of iPads currently in use in HE institutions across different countries, inevitably a number of related questions emerge: Does this tablet warrant special research interest vis-à-vis teaching and learning in HE? What is the possible contribution of iPads towards instruction? Are innovative pedagogies encouraged and facilitated through the use of iPads? In conclusion, is this tablet computer a game-changer and can it provide a transformative experience for teaching and learning? Such questions can only partially be addressed at any educational conference, and in the long term empirical studies will inevitably clarify the contribution of iPads towards teaching and learning in HE. The 1st International Conference on the Use of iPads in HE provided a necessary, useful, and at times critical forum for the presentation of a wide range of instructional applications in different disciplines. The papers reflect not only the enthusiasm of the respective authors, but also their concerns and future plans. As academics and researchers we are grateful for the shared knowledge and the opportunity to reflect on the use of iPads in HE. These proceedings provide fertile ground to continue to do so.
Keywords: iPads; Education; Higher Education